Salamanders aid research into mechanisms of non‐canonical organ regeneration for clinical applications - Binxu Yin; Xiao Cui; Yanmei Liu; Ji‐Feng Fei (Medicine Advances, 2024)
Abstract Salamanders possess remarkable regenerative capacities for organ regeneration among tetrapod vertebrates. Previous research has primarily focused on studying the regeneration of canonical tissues or organs such as limbs, tail, brain, spinal cord, heart, and lens. The advancements made in these areas have broader implications for understanding regeneration and developing therapeutic approaches for these organs, not only in salamanders but also in other vertebrates. In recent years, there has been an increasing interest in studying the regeneration of non‐canonical organs in salamanders, such as the liver, lungs, kidneys, and pancreas. This diversification of research has opened up new avenues and provided potential solutions to challenging clinical problems. This review aims to summarize the progress made in the field of non‐canonical organ regeneration in salamanders and provides an outlook on future research directions.